Retrospective survival analysis of stage II–III rectal cancer: tumour regression grade, grading and lymphovascular invasion are the only predictors. Issue 3 (14th December 2020) - Morini, Andrea; Annicchiarico, Alfredo; Romboli, Andrea; Ricco', Matteo; Crafa, Pellegrino; Montali, Filippo; Dell'Abate, Paolo; Costi, Renato
Abstract: Background: Tumour regression grade is gaining interest as a prognostic factor of patients undergoing neoadjuvant chemoradiotherapy and surgery for locally advanced rectal cancer. Methods: A series of 68 consecutive patients with locally advanced rectal cancer treated by neoadjuvant chemoradiotherapy and surgery between 2010 and 2016 was retrospectively studied. The impact on disease‐free survival (DFS) and overall survival (OS) of several criteria was analysed. Univariate analysis was performed through Kaplan–Meier statistics. Multivariate analysis was performed through Cox regression model. Using criteria found to be related to long‐term outcomes, a predictive model of patient's OS was calculated. Results: Poor tumour regression grade – TRG3 ( P = 0.010), poor grading – G3 ( P = 0.001) and lymphovascular invasion (LVI; P = 0.030) were associated with short OS at univariate analysis. OS was associated with TRG3 and G3 at multivariate analysis ( P = 0.016 and P = 0.027, respectively). DFS was associated with LVI ( P = 0.001), G3 tumours ( P = 0.046) and TRG3 ( P = 0.045) at univariate analysis. At multivariate analysis, only LVI was associated with DFS ( P = 0.041). A score, pondering the impact of three parameters (2 points for TRG3, 2 for G3 and 1 for LVI), was created and resulted to predict patient OS ( P = 0.008), ranging from 94.5 months (score = 0–1) to 32 months (score = 3–5). Conclusion: TRG3 and G3 were associated with poor OS, and LVI was the most significant predictor of DFS. An easy‐to‐use score may allow for a more accurate prediction of OS. Abstract : Management of extraperitoneal, locally advanced rectal cancer is neoadjuvant chemoradiotherapy followed by surgery. The records of 68 consecutive patients was retrospectively retrieved and studied. The aim of this study was to assess the impact of several criteria on survival of patients with locally advanced rectal cancer. Tumour regression grade 3 and G3 were associated with poor overall survival, and lymphovascular invasion was the most significant predictor of disease‐free survival.